2011
DOI: 10.1016/j.schres.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Age-related cortical thinning in schizophrenia

Abstract: Although the effects of aging on the neural correlates of schizophrenia have been researched for many years, no clear conclusion has been reached. While some studies have demonstrated progressive age-related gray matter reductions in schizophrenia, other studies have not found evidence of progression. Moreover, it remains unclear whether the influence of aging on global or regional cortical thickness differs between schizophrenia patients and healthy controls. This study aimed to confirm previous reports of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
36
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 38 publications
(48 reference statements)
11
36
5
Order By: Relevance
“…It represents a methodological alternative to volume measurements for the investigation of subtle cortical changes in the human brain (Dale et al, 1999;Fischl et al, 1999a). Prior studies examining cortical thickness in schizophrenia identified a broad pattern of reduced cortical thickness in the prefrontal regions, temporal regions, superior parietal gyrus, hippocampus and cingulate gyrus (Narr et al, 2005;Schultz et al, 2010b;Kubota et al, 2011;van Haren et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It represents a methodological alternative to volume measurements for the investigation of subtle cortical changes in the human brain (Dale et al, 1999;Fischl et al, 1999a). Prior studies examining cortical thickness in schizophrenia identified a broad pattern of reduced cortical thickness in the prefrontal regions, temporal regions, superior parietal gyrus, hippocampus and cingulate gyrus (Narr et al, 2005;Schultz et al, 2010b;Kubota et al, 2011;van Haren et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with schizophrenia, when compared with healthy controls, prefrontal and temporal cortices show reductions in cortical thickness and surface area, with relative sparing of more posterior regions (Kuperberg et al, 2003;Rimol et al, 2010;Nesvag et al, 2011;Kubota et al, 2011). Cortical surface parameters, like volumetric measures, vary with age and medication history (Wiegand et al, 2004;Nesvag et al, 2011;Kubota et al, 2011). Nevertheless, studies indicate that cortical surface parameters are linked to neurodevelopmental processes that undergo only partial reshaping across the lifespan (Wienberger and McClure, 2002;Mangin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(C) Scatter plots and regression slopes of regional mean cortical thickness with age in each ROI. The age regression slope within all ROIs did not significantly differ between groups (P value range = 0.215-0.960) (Kubota et al, 2011). across the course of the illness. Regarding this, current studies on first episode schizophrenia and at risk mental state (ARMS) subjects indicate that gray matter changes mainly occur in the period around illness onset (Borgwardt et al, 2007;Andreasen et al, 2011).…”
Section: Progressive Brain Disease Hypothesismentioning
confidence: 78%
“…Consequently, cross-sectional studies mainly deal with this concept. Thus, here we introduce our investigation on age effects on global and regional cortical thickness, using a crosssectional study design that accounts for subject age and disease duration (Kubota et al, 2011).…”
Section: Progressive Brain Disease Hypothesismentioning
confidence: 99%
See 1 more Smart Citation